Implementation of Lecturer Guidance to Students in Character Building in Islamic Higher Education - M. Baihaqi. Ma (Indonesian Journal of Society Development, 2022)
This devotional article aims to describe the implementation of lecturer guidance to students in character building at Islamic tertiary institutions. The purpose of this service is a form of the author's love for educational institutions in providing guidance so that there are changes in the moral, mental and spiritual character of today's students. The type of writing for this article is a qualitative service that seeks to describe and describe a portrait of the sincere and sincere dedication of lecturers that has been carried out at the Tarbiyah Al Wasliyah High School of Binjai City and then described in a structured manner by following the applicable rules of writing scientific papers. From the results of the dedication that has been carried out, it was found that: First, Islamic tertiary institutions play an important role by optimizing the campus as the epicenter of character building. Second, Islamic religious colleges as centers for the formation of religious moderation in the midst of religious pluralism. Third, Islamic tertiary institutions make lecturers not only as educators for students to improve their intellect alone but also as agents for the formation of students' moral and spiritual character. Fourth, lecturers at Islamic religious tertiary institutions are at the forefront of protecting the nation's religion and morals